Pemanfaatan Smartphone untuk Meningkatkan Pemahaman Peserta Didik pada Materi Adab Bersosial Media - Yuswandari, Ochy; Tentiasih, Septyana (ALSYS, 2025)
This study is motivated by social media as one of the main features in smartphones that has become a broad space for expression and interaction for students. Unfortunately, many students lack an understanding of the boundaries of good social media etiquette, such as maintaining politeness, not spreading hoaxes, respecting others' privacy, and avoiding hate speech. This phenomenon indicates an urgent need to provide digital character education to students, one of which is through learning about social media etiquette. The use of smartphones in learning social media etiquette aligns with contextual and constructivist approaches that emphasize the connection between the subject matter and students' real-life experiences. Based on this description, this study is important to examine the extent to which the use of smartphones can enhance students' understanding of social media etiquette, while also serving as a strategic effort in shaping the digital character of the younger generation in the era of information technology. The purpose of this study is to determine how smartphones influence the improvement of students' understanding and etiquette in social media. The method used is a qualitative approach with a descriptive method, involving a sample of 23 participants selected through purposive random sampling technique. Data were collected through interviews, observations, and documentation. The results indicate that the use of smartphones provides a unique appeal for students and facilitates their understanding of social media etiquette when delivered through the media they use daily, as it is more interactive and aligned with their digital habits. Additionally, changes in students' digital attitudes began to be evident after the learning, such as avoiding hate speech and respecting privacy on social media.